2005
DOI: 10.1111/j.1743-6109.2005.20106.x
|View full text |Cite
|
Sign up to set email alerts
|

The Labial Photoplethysmograph: A New Instrument for Assessing Genital Hemodynamic Changes in Women

Abstract: Aim The labial photoplethysmograph (LP), a new measure for assessing genital responses in women, was compared to the vaginal photoplethysmograph (VP). Methods Fifteen women wore both devices simultaneously while viewing neutral, sexual, sexually-threatening, and threatening film clips. Results The LP and VP exhibited comparable specificity to sexual stimuli. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 15 publications
(18 reference statements)
2
43
0
1
Order By: Relevance
“…This limits instrumentation artifacts in comparing men and women and enhances the applicability of the methodology. The use of both positive and anxiety arousal control groups in our study also provided strong discriminant validity for genital temperature as a measure of sexual arousal and was in line with previous research using such control groups (Both et al, 2003;Kukkonen et al, 2007;Laan, Everaerd, & Evers, 1995;Prause et al, 2005). Furthermore, the data collected from a non-college age sample allowed us to generalize the methodology to a broader population and supported the results from our previous research (Kukkonen et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This limits instrumentation artifacts in comparing men and women and enhances the applicability of the methodology. The use of both positive and anxiety arousal control groups in our study also provided strong discriminant validity for genital temperature as a measure of sexual arousal and was in line with previous research using such control groups (Both et al, 2003;Kukkonen et al, 2007;Laan, Everaerd, & Evers, 1995;Prause et al, 2005). Furthermore, the data collected from a non-college age sample allowed us to generalize the methodology to a broader population and supported the results from our previous research (Kukkonen et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Finally, the inclusion of a measure of instrument intrusiveness provided valuable information on the perceived effect of the camera on sexual arousal and supported the ecological validity of the technique. Very few Prause et al (2005) found a highly significant correlation between perceived discomfort of both the vaginal and labial photoplethysmographs and their level of interference in attending to films, which suggests that having an instrument that requires no contact would circumvent this distraction. It could be argued, however, that in the case of thermography, having a camera record genital temperature can differentially affect participants with varying levels of dispositional self-consciousness, something that was not measured in this study but should be examined in future research (Meston, 2006;van Lankveld, van den Hout, & Schouten, 2004).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This measurement feature is desirable, because it minimizes data transformations. However, full return-to-baseline appears to occur rarely (for exception see Prause, Cerny, & Janssen, 2005). Evidence across multiple measurement domains now suggests that returning to baseline after a period of sexual stimulation typically is a long process for women.…”
Section: Discussionmentioning
confidence: 93%